Analisis Pengaruh Coaching dan Komunikasi terhadap Employee Engagement melalui Loyalitas pada PT. Bank X (Persero) Tbk., Kantor Regional X Sulawesi dan Maluku - Widiawaty Mochtar; Rosnaini Daga; Abdul Samad A (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2025)
This research aims to determine and analyze the Influence of Coaching and Communication variables on Employee Engagement through Loyalty at PT. Bank X (Persero) Tbk., Regional Office X Sulawesi and Maluku. The analytical tool used in this research is data analysis using SEM-PLS. The population in this study were all employees of PT. Bank X (Persero) Tbk., Regional Office X Sulawesi and Maluku with 2,140 employees. Using purposive sampling technique, so the sample used is all permanent employees of PT. Bank X (Persero) Tbk., Regional X Office with a certain level, namely 119 employees. Research results show that : (1) Coaching has a positive and significant effect on Loyalty at PT. Bank X (Persero) Tbk., Regional X Office, (2) Communication has a positive and significant effect on Loyalty at PT. Bank X (Persero) Tbk., Regional X Office, (3) Coaching has a positive and significant effect on Employee Engagement at PT. Bank X (Persero) Tbk., Region X Office, (4) Communication has a positive and significant effect on Employee Engagement at PT. Bank X (Persero) Tbk., Regional X Office (5) Loyalty has a positive and significant effect on Employee Engagement at PT. Bank X (Persero) Tbk., Regional X Office, (6) Coaching has a positive and significant effect on Employee Engagement through Loyalty to PT. Bank X (Persero) Tbk., Region X Office (7) Communication has a positive and significant effect on Employee Engagement through Loyalty to PT. Bank X (Persero) Tbk., Regional X Office.